Convergence excess esotropia treated surgically with fadenoperation and medical rectus muscle recessions. - Leitch, R. J. (1990)
Convergence excess esotropia has been treated with bifocals, miotics, medial rectus recession(s), fadenoperation, or a combination of these. However, comparatively few studies on the sensory status of these patients exist. We present the sensory findings in 31 children treated surgically. Twenty-one had fadenoperations combined with bimedial rectus recessions, one had a fadenoperation alone, and nine had augmented bimedial rectus recessions. Five children (16%) achieved bifoveal fusion, 22 (71%) had varying degrees of peripheral fusion, and four (13%) had no detectable binocularity after a mean postoperative follow-up of 2.4 years.